The Centrality of Conflict Transformation in Solving Political Struggles and Political Violence in South Sudan (The Strategic Review for Southern Africa, 2020)
South Sudanese have borne the brunt of the civil wars that have engulfed the country since 1955 to the present. People are perishing at the hands of government soldiers, militias and rebel forces. Using document analysis, this article evaluates the centrality of the conflict transformation model in reducing political violence in South Sudan. Political struggles and political violence in South Sudan have significantly led to the deterioration of human security and human rights. Conflict transformation helps South Sudan in realising that there is more to their future as a country rather than power struggles largely driven by ethnic politics. The North-South divide has since diminished. This implies that tolerance should now prevail. The DinkaNuer dichotomy should be a cause for celebration rather than animosity. It is significant for the country’s political leaders to realise that ethnic differences are going to forever be part of their lives, and should therefore be a source of strength as they seek to rebuild their country. The transformation of relationships is thus essential in eliminating the so-called ‘politics of isolation’ in the country and ensuring that violence is not viewed as the solution to the problems affecting the country.